Influence of Social Simulation Learning Strategy in Improving Social Intelligence and Talking Children in Raudhatul Athfal Jamiyatushalihin Medan - Anisah Anisah; Khadijah Khadijah; Akmal Walad Ahkas (Budapest International Research and Critics in Linguistics and Education (BirLE) Journal, 2020)
This study aims to uncover and explain and know: (1) the effect of social simulation learning strategies on children's social intelligence in Raudhatul Athfal Jamiyatushalihin Medan, (2) the effect of social simulation learning strategies on children's speaking in Raudhatul Athfal Jamiyatushalihin Medan, and (3) the influence of social simulation learning strategies on social intelligence and children's talking together at Raudhatul Athfal Jamiyatushalihin Medan. The research method used is quantitative with an experimental approach. The research sample consisted of two classes each one experimental class and one control class. The instrument used in the study was observation and documentation. The analysis technique used is analysis of variance The research findings show: (1) the influence of social simulation learning strategies on children's social intelligence in Raudhatul Athfal Jamiyatushalihin Medan, (2) there is an influence of social simulation learning strategies on children's speaking in Raudhatul Athfal Jamiyatushalihin Medan, and (3) there is an influence on simulation learning strategies social towards social intelligence and talking to children together in Raudhatul Athfal Jamiyatushalihin Medan.